RETRACTED: Investigating Relationships Between Tourism, Economic Growth, and CO2 Emissions in Brazil: An Application of the Nonlinear ARDL Approach - Ullah, Irfan; Rehman, Alam; Svobodova, Libuse; Akbar, Ahsan; Shah, Muhammad Haroon; Zeeshan, Muhammad; Rehman, Mubeen Abdur (Frontiers in Environmental Science, 2022)
Global tourism has witnessed a significant positive implication on the development of developing economies. Despite the positive implication of tourism, it imposes a serious environmental cost such as environmental pollution. Brazil receives a large number of tourists each year that potentially affects economic growth and development. Therefore, this study investigates the effect of tourism on GDP and CO2 emissions in Brazil. We used a Non-linear ARDL approach to examine the nexus between tourism, economic growth, and CO2 emissions in Brazil for the period 1995-2018. The outcomes of this study reveal both short-run and long-run associations between tourism, GDP per capita, and CO2 emissions in Brazil. Nevertheless, both tourism and economic growth cause significant deterioration of the environment quality in Brazil. These findings suggest that the policymakers shall look for more sustainable and eco-friendly economic growth and tourism policies to preserve the environmental quality in Brazil.